2019
DOI: 10.1128/aem.00383-19
|View full text |Cite
|
Sign up to set email alerts
|

Plantibacter flavus, Curtobacterium herbarum, Paenibacillus taichungensis, and Rhizobium selenitireducens Endophytes Provide Host-Specific Growth Promotion of Arabidopsis thaliana, Basil, Lettuce, and Bok Choy Plants

Abstract: A collection of bacterial endophytes isolated from stem tissues of plants growing in soils highly contaminated with petroleum hydrocarbons were screened for plant growth-promoting capabilities. Twenty-seven endophytic isolates significantly improved the growth of Arabidopsis thaliana plants in comparison to that of uninoculated control plants. The five most beneficial isolates, one strain each of Curtobacterium herbarum, Paenibacillus taichungensis, and Rhizobium selenitireducens and two strains of Plantibacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 83 publications
1
16
0
Order By: Relevance
“…Thus, the interactions between Bradyrhizobium and Rhizobium or Burkholderia is direct or indirect, which might be regulated by the complex relationship between rhizobacteria and host plants. Overall, these results point to complex microbe-microbe interactions in peanut rhizosphere communities and suggest that exogenous bradyrhizobia inoculants increase the relative abundances of potentially PGPR populations, since both Rhizobium and Burkholderia are PGPR (Vurukonda et al 2018;Mayer et al 2019).…”
Section: Alternation In Peanut Plant Rhizobacterial Communities By Bradyrhizobia Inoculationmentioning
confidence: 81%
See 1 more Smart Citation
“…Thus, the interactions between Bradyrhizobium and Rhizobium or Burkholderia is direct or indirect, which might be regulated by the complex relationship between rhizobacteria and host plants. Overall, these results point to complex microbe-microbe interactions in peanut rhizosphere communities and suggest that exogenous bradyrhizobia inoculants increase the relative abundances of potentially PGPR populations, since both Rhizobium and Burkholderia are PGPR (Vurukonda et al 2018;Mayer et al 2019).…”
Section: Alternation In Peanut Plant Rhizobacterial Communities By Bradyrhizobia Inoculationmentioning
confidence: 81%
“…4 and S8; Table S8). Since CCBAU 051107 T treatment had the most specific hub taxa in the harvest stage, including Bradyrhizobium, which is well known symbiotic nitrogen fixers associated with leguminous plants to promote plants growth, and also used as PGPR for non-legumes including peppers, radishes and tomatoes by producing auxins and siderophores (Antoun et al 1998;Mayer et al 2019). Therefore, these results indicated that the inoculation of bradyrhizobia might have profound impacts on the host plant growth via the regulation of complex interaction networks of rhizobacteria.…”
Section: Alternation In Peanut Plant Rhizobacterial Communities By Bradyrhizobia Inoculationmentioning
confidence: 92%
“…sp D4-14 inhibited the growth of barley and oats. Curtobacterium has been found to associate with roots and promote plant growth in Arabidopsis , lettuce, basil, red clover and cucumber 55 57 .…”
Section: Discussionmentioning
confidence: 99%
“…sp D4-14 inhibited the growth of barley and oats. Curtobacterium has been found to associate with roots and promote plant growth in Arabidopsis, lettuce, basil, red clover and cucumber [56][57][58].…”
Section: Seed Microbiomes Enrich For Microbes That Promote Root Growtmentioning
confidence: 99%